Significant northwest shift in suitable climate expected for North American bison by the year 2100 - Shupinski, Alex B.; Martin, Jeff M.; Brock, Brent L.; Otárola-Castillo, Erik; Hill, Matthew E.; Widga, Chris; Rudnik, Joshua L.; Short, Rachel A. (Frontiers in Ecology and Evolution, 2026)
IntroductionMany species are shifting their geographic ranges in response to changing climate, and identifying climate impacts on future species distributions will be critical for conservation success. North American bison (Bison bison) provide an exceptional study system for exploring the use of an interdisciplinary record of paleontological, archaeological, and historical data for conservation due to the plethora of past occurrences across a large geographic and temporal scale, in combination with their “near-threatened” designation by the IUCN Red List because of current small, fragmented populations following a near-extinction event in the 1880s. Moreover, the multiple identities of bison as free-roaming wildlife, as wildlife with limitations, and as captive semi-domesticated livestock introduce unique conservation concerns across the four sectors of the Bison Management System (BMS; Tribal, private, public, nonprofit-NGO).MethodsTo model bison climate suitability using “Bioclim”, we associated 1,774 bison occurrences over the last 21,000 years with three PastClim variables (warmest temperature of the warmest month, temperature seasonality, and precipitation of the coldest quarter) that were identified as the strongest predictors of past bison distributions using a variance inflation factor. The model was projected onto the WorldClim RCP4.5 and RCP8.5 future climate scenarios for the four remaining 20-yearperiods to 2100 CE and onto the WorldClim 2.1 version of current climate, to determine expected changes in climate suitability.ResultsThe distribution of suitability scores changes rapidly, shifting significantly between each 20-year interval until the end of the century. By 2100, the centroid of suitable climate, using the standard 50% threshold, is expected to shift from its current location near the 49th parallel to the northwest and toward the northern border of Canada by 1,182 km under the RCP4.5 climate scenario and 2,254 km under the RCP8.5 climate scenario. Suitability ranges above the optimal minimal threshold identified by the receiving operator characteristic (8.5%) are also predicted to shift to the northwest by 793 km under RCP4.5. and 1267 km under RCP8.5.DiscussionWith an anticipated geographic shift in the most suitable bison climate, it is necessary to prepare future management strategies for BMS sectors to maintain a sustainable relationship with bison.